Pattern of poultry diseases brought at Veterinary Teaching Hospital (VTH), Rampur and National Avian Disease Investigation Laboratory (NADIL), Bharatpur, Chitwan, Nepal during 2017/18 (Nepalese Veterinary Journal, 2023)
Available within a full text